Development of Thematic Teaching Materials Using the Kvisoft Flipbook Maker Application with 4-D models in Elementary Schools - Yulia Maulani; Nur Azmi Alwi (AL-ISHLAH: Jurnal Pendidikan, 2023)
The rapid development of technology has had a significant impact on various sectors, especially in the field of education. One of the developments in the field of education is electronic teaching materials. The data obtained in this study were obtained from observation and analysis of the needs of teachers and students at three state elementary schools in west sumatra. The method to be used in this research activity uses Research and Development (RD) using the 4D model. The 4-D model consists of four stages, namely defining design, development and implementation. Prior to performance, the product first goes through the validity stage by experts in their respective fields, researching using aspects of language, content, presentation and graphics to carry out validity. However, because some of the constraints of this research only extend to development, after expert validation tests and practicality of students and teachers have been carried out, it can be concluded that thematic teaching materials using the inquiry method-based Flipbook application are categorized as very valid and can be implemented.